Efeitos da suplementação lipídica sobre o desempenho, metabolismo e perfil de ácidos graxos no leite em vacas leiteiras - Gallardo, Walter Bedon (2020)
Our objective was to investigate how lipid supplementation affects the performance, metabolism and fatty acid profile in milk in dairy cows. A data set was created using 105 peer-review papers (266 treatment averages from 115 studies). The effects were compared by the mean gross difference between diets with lipid supplementation and control diets (without lipid supplementation). Lipid sources were divided into 10 groups. The level of inclusion of lipids (ether extract (EE) per kg of dry matter (DM)) was divided into three classes: <50 g, 50 to 70 g and >70 g EE/kg DM. The lactation stage was grouped into four classes of lactation days (DL): <60, 60 a 100, 100 a 200 and >200 DL. The level of heterogeneity was analyzed using I2 statistics. In general, lipid supplementation in the diet reduced the consumption of dry matter (DMI) by 0.33 kg/day, increased the digestibility of organic matter in the diet, but did not affect the consumption of digestible organic matter. Lipid supplementation reduced on average 9% the ruminal concentration of N-NH3 and by 11.9% the enteric emission of methane in relation to the control diet, which indicates an improvement in the ruminal efficiency of use of dietary N and carbon. Lipid supplementation increased milk production by 0.55 kg/day, which combined with the reduction in dry matter consumption increased feed efficiency by an average of 4%. Lipid supplementation reduced the levels of fat and protein in milk, reduced the proportion of saturated acids on average by 8.2% and increased the proportion of unsaturated fatty acids in milk by 16.2%. In addition, lipid supplementation increased on average 36.8% the proportion of C18: 2 cis 9, trans 11 in milk. However, the effects of lipid supplementation showed high heterogeneity and were mainly affected by the source and level of inclusion of EE in the diet. Calcium salts of unsaturated fatty acids, calcium salts of saturated and unsaturated fatty acids, saturated fatty acid of animal and vegetable origin, fish oil and algae are the most effective sources for increasing milk production. The use of traditional sources of lipids such as oilseeds and oil from vegetals does not influence milk production. Richer sources of unsaturated fatty acids xii and available for ruminal biohydrogenation are more effective in reducing the emission of rumen methane and improving the profile of fatty acids in milk. To obtain productive responses, supplementation with lipids is recommended to achieve ether extract levels between 50 to 70 g/kg of DM in the diet.